Electrical installation calculations : for compliance with BS 7671 : 2008 - Jenkins, Brian D. (Brian David); Coates, M. (Mark) (New York : Wiley-Blackwell, 2010)
'This book focuses on worked examples and keeps associated theoretical aspects to a minimum, furnishing the reader with the knowledge to carry out the necessary checks to electrical cable sizing software programmes . The book covers cross-sectional areas of circuit live conductors, voltage drop under normal load conditions, and earth fault loop impendances'--
Includes index.
Keywords: Electric wiring -- Mathematics; Electric wiring -- Standards -- Great Britain